Проблемы преобразования нелинейных систем управления технологическими процессами к эквивалентным линейным в форме Бруновского - Дмитриенко, Валерий Дмитриевич; Леонов, Сергей Юрьевич; Заковоротный, Александр Юрьевич; Главчев, Дмитрий Максимович (ВМВ, 2018)
Рассматривается задача линеаризации математических моделей, описывающих технологические процессы, с целью получения удобного инструмента для управления ими. Задача линеаризации решается с помощью геометрической теории управления (ГТУ). Привлекательность ГТУ связана с получением эквивалентных нелинейным моделям линейных моделей, которые удобно использовать для решения задач управления, получая структуры регуляторов или законы управления. После чего осуществляется обратный переход из пространства линейных систем в пространство исходной нелинейной системы. При этом основные аналитические преобразования автоматизированы с помощью специализированного программного обеспечения. Поиск функций преобразования, связывающих переменные линейной и нелинейной моделей, осуществляется с помощью нового конструктивного метода решения системы дифференциальных уравнений в частных производных.

The problem of linearization of mathematical models describing technological processes with the purpose of obtaining a convenient tool for managing them is considered. The problem of linearization is solved by means of a geometric control theory (GCT). The attractiveness of GCT is connected, first of all, with obtaining equivalent nonlinear linear models, which are convenient for solving management problems and receiving regulatory structures or control laws. After that performed the reverse transition from the space of linear systems to the space of the original nonlinear system. A wider application of the geometric control theory is hindered by cumbersome analytical transformations connected with the calculation of the derivatives and the Lie brackets, the definition of the involutivity of distributions, and so on, and also the problem of determining the transformation functions connecting the variables of linear models in the form of Brunovsky and initial non-linear models of control objects. The authors developed specialized software that automates the main analytical transformations of GCT. The search for the transformation functions connecting the variables of the linear and nonlinear models is carried out using a new constructive method for solving the system of partial differential equations.
Problems of transformation non-linear control systems of technological processes to equivalent linear in the form of Brunovsky
Keywords: геометрическая теория управления; программное обеспечение; функции преобразования; дифференциальные уравнения; linearization of the mathematical model; technological processes; geometric control theory; software; conversion functions